A fixed-dose 24-hour regimen of artesunate plus sulfamethoxypyrazine-pyrimethamine for the treatment of uncomplicated Plasmodium falciparum malaria in eastern Sudan - Osman Maha E; Khalil Insaf F; Magzoub Mamoun; Adam Ishag; Alifrangis Michael; Elmardi Khalid A (BMC, 2006)
Abstract Background Artemisinin-based combination therapy is increasingly being adopted as first-line antimalarial therapy. The choice of appropriate therapy depends on efficacy, cost, side effects, and simplicity of administration. Methods the efficacy of fixed co-formulated (f) artesunate-sulfamethoxypyrazine-pyrimethamine (AS+SMP f) administered at time intervals of 12 hours for a 24-hour therapy was compared with the efficacy of the same drug given as a loose combination (AS+SMP l) with a dose interval of 24 hours for 3 days for the treatment of uncomplicated Plasmodium falciparum malaria in eastern Sudan. Results seventy-three patients (39 and 34 in the fixed and the loose regimen of AS+SMP respectively) completed the 28-days of follow-up. On day 3; all patients in both groups were a parasitaemic but one patient in the fixed group of AS+SMP f was still febrile. Polymerase chain reaction genotyping adjusted cure rates on day 28 were 92.3% and 97.1% (P > 0.05) for the fixed and loose combination of AS+SMP respectively. Three (4.1%) patients (one in the fixed and two patients in the loose group of AS+SMP) in the study suffered drug-related adverse effects. Gametocytaemia was not detected during follow-up in any of the patients. Conclusion both regimens of AS+SMP were effective and safe for the treatment of uncomplicated P. falciparum malaria in eastern Sudan. Due to its simplicity, the fixed dose one-day treatment regimen may improve compliance and therefore may be the preferred choice.